Role of local physician in the early detection of maxillofacial neurogenic disorders - Irina K. Lutskaya (LLC "MEDIAFORMAT", 2022)
Various systemic diseases may me accompanied by or combined with sensory disturbances of maxillofacial region. In such cases the patients complain of pain or paresthesia, which could be local or central. The patients usually contact their local primary care physicians. The physician not only determines the diagnosis and prescribes treatment in accordance with his/her specialty, but also determines the algorithm for further examination. Knowlege of the main symptoms of neurogenic disorders makes it possible to refer the patient to specialty physician, such as dentist or neurologist, for the professionally directed diagnosis and treatment of certain manifestations of the local and central disorders, affecting the nervous system.